Memory B Cells Display Changes In The Expression Pattern Of Genes Related To Cell Survival In Elderly Individuals - Baez, Alicia; Alvarez-Laderas, Isabel; Piruat, Jose Ignacio; Caballero-Velazquez, Teresa; Millan-Ucles, Africa; Barbado, María Victoria; Medrano, Mayte; Garcia-Guerrero, Estefania; Sanchez-Abarca, Luis Ignacio; Perez-Simón, Jose Antonio; Espigado, Ildefonso (Blood, 2013)
Memory B cells (MBCs) have a very long half-life, remaining viable in a quiescent state for years. However, elderly individuals have less amount of MBCs and they produce lower amounts of antibodies. Thus, in aged individuals immunization become less efficient in terms of quantity and quality. Furthermore, several hematologic malignancies involving B-cell lineage, such as non-Hodgkin lymphomas, chronic lymphocytic leukemia or multiple myeloma, are increasingly common in aging population. With this background, we analyzed the gene expression patterns of naïve B cells (NBCs) versus MBCs in both younger and older subjects, in order to identify genes related to longevity that could be altered in the elderly population and related to an increased risk of developing certain lymphoid malignancies. NBCs and MBCs were obtained by immunomagnetic separation from buffy coats of 10 healthy donors: 5 young (20-25 years) and 5 elderly (65-70 years). By microarray techniques we analyzed the expression of 45000 genes in all samples. Unsupervised hierarchical clusters of gene expression data were performed using the average linkage and the Euclidean distance. To identify differentially expressed genes between experimental groups we applied non-parametric Mann-Whitney test. The differences in expression with a p value < 0.05 were considered significant. All analyses were performed using the Multi-experiment Viewer 4.7.1 software. Firstly, we confirmed that the expression pattern of NBCs versus MBCs is significanly different in 3548 genes in young and 2145 genes in elderly individuals. Next, in order to evaluate the effect of age in NBCs and MBCs, we compared the gene expression pattern of young versus aged subjects in both cell populations. Interestingly, we did not find significant differences in the naïve population between young and aged individuals, whereas we found 1593 genes differentially expressed in young versus elderly subjects within MBCs; therefore, age affects the gene expression pattern of MBCs but not NBCs. Furthermore, we identified 467 genes which displayed a higher or lower expression in MBCs from aged as compared to younger individuals and NBCs, most of them involved in proliferation and cell cycle, apoptosis, cell survival and hematological diseases (Table 1). Table 1Top FunctionsGene expressionDown-regulatedUp-regulatedCell death and survival, Gene expression.ACTR3, BMP6, CALCOCO2, CFLAR, CRTC2, DCTN3, FDPS, GCN1L1, IL6, KLF6, MAP4K4, MEF2C, NFKB1, SEC31A, SMAD3, ZNF271ATM, BMI1, CCND1, DAZ2, IGHG1, IRF1, NR1H2, PCNA, RPS14, SOCS7, TGFB1, TNIP1, UBCCell cycle, Cancer.AK1, CCNG2, CUL1, CUL4A, FOXO1, GNL3, GTF2I, RB1, RBL2, RBX1, RPL23, SLC25A5, THBS1ALDH4A1, CDKN1B, CRADD, CSNK1A1, FHL1, FLRT2, HGF,ID3, RBL1, RGS12, SLC6A6, TP53Cellular development, Cellular growth and proliferation, Hematological system development and function.CAV1, CD69, IL21R, ILK, ITGB3, MAPK14, PLAC8, PTPN11, RPL6, SH2B3, TP53INP1,VAV3AKT1, BRAF, CCDC88A, IRAK1, KIT, MAP2K6, PRKCD, PTPN6, RPS2, SP1, SYK, TLX1, VEGFAEmbryonic development, Organismal development, Tissue development.ARIH2, ATG16L1, CAPZA2, DYNLT3, GUSB, M6PR, SATB1, SKAP1, SMAD2, SMAD3, TAOK1, TMEM2ATP1B2, BSG, CACNG2, CCDC50, CHD4, DSTN, GRID2, PASK, PLEC, SF3B3Infectious disease, Inflammatory diseaseCCDC90B, DAD1, DNAJC10, NCSTN, NDUFS1, NSMAF, PSEN1, RASSF1, SEC23A, SENP6, SRP19, TNFAIP2GNAZ, LAMC2, MOAP1, PPIB, SF1, TNFRSF21Antigen presentation, Cell-to-Cell signaling and interaction, Cell-mediated immune responseARHGDIB, CNOT7, HNRNPA3, RPL6, RPS3A, SF3B1, ZC3HAV1BST2, EIF4A2, GBP4, PLXNB1, PPIA, RPL13A, RYR1 Gene expression profiles of NBCs and MBCs are different. While there are no significant differences in NBCs of young versus elderly individuals, we detected significant differences in expression patterns of MBCs between both age groups, which indicates that MBCs could be more susceptible to age related alterations. No relevant conflicts of interest to declare.